Enhanced production of gibberellin A(4) (GA(4)) by a mutant of Gibberella fujikuroi in wheat gluten medium - Lale, Geetanjali; Gadre, Ramchandra V. (Journal of Industrial Microbiology & Biotechnology, 2010)
Mutants of Gibberella fujikuroi with different colony characteristics, morphology and pigmentation were generated by exposure to UV radiation. A mutant, Mor-189, was selected based on its short filament length, relatively high gibberellin A(4) (GA(4)) and gibberellin A(3) (GA(3)) production, as well as its lack of pigmentation. Production of GA(4) by Mor-189 was studied using different inorganic and organic nitrogen sources, carbon sources and by maintaining the pH of the fermentation medium using calcium carbonate. Analysis of GA(4) and GA(3) was done by reversed-phase high-performance liquid chromatography and LC-MS. The mutants of G. fujikuroi produced more GA(4) when the pH of the medium was maintained above 5. During shake flask studies, the mutant Mor-189 produced 210 mg l(-1) GA(4) in media containing wheat gluten as the nitrogen source and glucose as the carbon source. Fed-batch fermentation in a 14 l agitated fermenter was performed to evaluate the applicability of the mutant Mor-189 for the production of GA(4). In 7-day fed-batch fermentation, 600 mg l(-1) GA(4) were obtained in the culture filtrate. The concentration of GA(4) and GA(3) combined was 713 mg l(-1), of which GA(4) accounted for 84% of the total gibberellin. These values are substantially higher than those published previously. The present study indicated that, along with maintenance of pH and controlled glucose feeding, the use of wheat gluten as the sole nitrogen source considerably enhances GA(4) production by the mutant Mor-189.
Keywords: Fermentation; GA(4); Gibberella fujikuroi; Mutant; Wheat gluten